Externally Delivered Focused Ultrasound for Renal Denervation - Neuzil, Petr; Ormiston, John; Brinton, Todd J; Starek, Zdenek; Esler, Murray; Dawood, Omar; Anderson, Thomas L; Gertner, Michael; Whitbourne, Rob; Schmieder, Roland E (JACC. Cardiovascular interventions, 2016)
OBJECTIVES: The aim of this study was to assess clinical safety and efficacy outcomes of renal denervation executed by an externally delivered, completely noninvasive focused therapeutic ultrasound device. BACKGROUND: Renal denervation has emerged as a potential treatment approach for resistant hypertension. METHODS: Sixty-nine subjects received renal denervation with externally delivered focused ultrasound via the Kona Medical Surround Sound System. This approach was investigated across 3 consecutive studies to optimize targeting, tracking, and dosing. In the third study, treatments were performed in a completely noninvasive way using duplex ultrasound image guidance to target the therapy. Short- and long-term safety and efficacy were evaluated through use of clinical assessments, magnetic resonance imaging scans prior to and 3 and 24 weeks after renal denervation, and, in cases in which a targeting catheter was used to facilitate targeting, fluoroscopic angiography with contrast. RESULTS: All patients tolerated renal denervation using externally delivered focused ultrasound. Office blood pressure (BP) decreased by 24.6 ± 27.6/9.0 ± 15.0 mm Hg (from baseline BP of 180.0 ± 18.5/97.7 ± 13.7 mm Hg) in 69 patients after 6 months and 23.8 ± 24.1/10.3 ± 13.1 mm Hg in 64 patients with complete 1-year follow-up. The response rate (BP decrease >10 mm Hg) was 75% after 6 months and 77% after 1 year. The most common adverse event was post-treatment back pain, which was reported in 32 of 69 patients and resolved within 72 h in most cases. No intervention-related adverse events involving motor or sensory deficits were reported. Renal function was not altered, and vascular safety was established by magnetic resonance imaging (all patients), fluoroscopic angiography (n = 48), and optical coherence tomography (n = 5). CONCLUSIONS: Using externally delivered focused ultrasound and noninvasive duplex ultrasound, image-guided targeting was associated with substantial BP reduction without any major safety signals. Further randomized, sham-controlled trials will be needed to validate this unique approach.
Keywords: Equipment Design; autonomní denervace; Kidney; Magnetic Resonance Imaging; Drug Resistance; hypertenze; Europe; Female; výsledek terapie; ženské pohlaví; Australia; léková rezistence; Time Factors; časové faktory; lidé; Evropa; Autonomic Denervation; magnetická rezonanční tomografie; duplexní dopplerovská ultrasonografie; New Zealand; Treatment Outcome; Nový Zéland; ablace intenzivním ultrazvukovým paprskem; krevní tlak; Austrálie; chirurgické vybavení; arteria renalis; Middle Aged; Hypertension; Male; Aged; lidé středního věku; Ultrasonography, Doppler, Duplex; Antihypertensive Agents; senioři; mužské pohlaví; antihypertenziva; angiografie; design vybavení; ledviny; Blood Pressure; High-Intensity Focused Ultrasound Ablation; Surgical Equipment; Angiography; Renal Artery; Humans